2015
DOI: 10.1007/s10589-015-9784-y
|View full text |Cite
|
Sign up to set email alerts
|

Dirichlet control of elliptic state constrained problems

Abstract: We study a state constrained Dirichlet optimal control problem and derive a priori error estimates for its finite element discretization. Additional control constraints may or may not be included in the formulation. The pointwise state constraints are prescribed in the interior of a convex polygonal domain. We obtain a priori error estimates for the L 2 (Γ)-norm of order h 1−1/p for pure state constraints and h 3/4−1/(2p) when additional control constraints are present. Here, p is a real number that depends on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…We leave this to be considered elsewhere. For a 2D convex polygonal domain and f = 0, we use a recent regularity result of Mateos and Neitzel [32] below to give conditions on the domain and y d to guarantee the solution has the above regularity. For a higher dimensional convex polyhedral domain, the regularity theory is much more complicated, and we do not attempt to provide conditions to guarantee the above regularity in this work.…”
Section: Background: the Optimality System And Regularitymentioning
confidence: 99%
“…We leave this to be considered elsewhere. For a 2D convex polygonal domain and f = 0, we use a recent regularity result of Mateos and Neitzel [32] below to give conditions on the domain and y d to guarantee the solution has the above regularity. For a higher dimensional convex polyhedral domain, the regularity theory is much more complicated, and we do not attempt to provide conditions to guarantee the above regularity in this work.…”
Section: Background: the Optimality System And Regularitymentioning
confidence: 99%
“…Researchers have performed numerical analysis of computational methods for Dirichlet boundary control problems for over a decade. Many researchers considered the standard finite element method and obtained an error estimate for the optimal control of order h s for all s < min{1, π/2ω}, where ω is the largest angle of the boundary polygon; see, e.g., [8,36,37]. Apel et al in [1] considered special meshes and obtained an optimal convergence rate with s < min{3/2, π/ω − 1/2}.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, the argumentation is restricted to unconstrained problems. For the error of the controls in L 2 (Γ), the order shown in [9] is not improved.Nevertheless, the regularity of the control and the existing numerical experiments, see [18,17], suggested that for the control variable the order should be greater: h s for all s < min(1, π/ω 1 − 1/2) if one uses standard quasi-uniform meshes, and for all s < min(3/2, π/ω 1 − 1/2) if one uses certain quasi-uniform meshes which allow for superconvergence effects, see Definition 4.5. Our main results, Theorems 4.1 and 5.3, fully explain the observed orders of convergence in the literature for the control variable, improve existing results for the state variable in constrained linear-quadratic problems posed in convex domains, and provide the first available results in nonconvex domains.…”
mentioning
confidence: 99%